PREVALENCE OF OBESITY IN AFFLUENT SCHOOL CHILDREN IN MULTAN - Muhammad Junaid (Army Medical College Rawalpindi, 2021)
Objective: The objective of this study was to determine the prevalence of obesity in affluent school children in Multan.